EASY WAYS TO TEACH A FOREIGN LANGUAGE TO YOUNG CHILDREN - Mo'minova Madinabonu (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article discusses methods of teaching foreign languages to young children. Teaching a language to a child is a challenging and exhausting task: it demands some basicknowledge and strong scientific background. Teaching teachers how to teach children is even a moreresponsible task as there are no magical tricks when we deal with children. Teaching foreign languages to young children is not difficult, it is interesting and entertaining. It can be foundation of their perfect of learning that language in the future.